Unanticipated Rapid Remission of Refractory Bulimia Nervosa, during High-Dose Repetitive Transcranial Magnetic Stimulation of the Dorsomedial Prefrontal Cortex: A Case Report - Downar, Jonathan; Sankar, Ashwin; Giacobbe, Peter; Woodside, Blake; Colton, Patricia (Frontiers in Psychiatry, 2012)
A woman with severe, refractory bulimia nervosa underwent treatment for comorbid depression using repetitive transcranial magnetic stimulation (rTMS) of the dorsomedial prefrontal cortex (DMPFC) using a novel technique. Unexpectedly, she showed a rapid, dramatic remission from bulimia nervosa. For 5 months pre-treatment, she had reported two 5-hour binge-purge episodes per day. After rTMS session 2 the episodes stopped entirely for 1 week; after session 10 there were no further recurrences. Depression scores improved more gradually to remission at session 10. Full remission from depression and binge-eating/purging episodes was sustained more than 2 months after treatment completion. In neuroimaging studies, the DMPFC is important in impulse control, and is underactive in bulimia nervosa. DMPFC-rTMS may have enhanced the patient’s ability to deploy previously acquired strategies to avoid binge-eating and purging via a reduction in her impulsivity. A larger sham-controlled trial of DMPFC-rTMS for binge-eating and purging behavior may be warranted.